Pemanfaatan Digital Marketing Pada UMKM Dalam Meningkatkan Penjualan pada Kelurahan Tebing Tinggi Kecamatan Padang Hilir Kota Tebing Tinggi - Syafrizal, Rodi; Nursaimatussaddiya, Nursaimatussaddiya; Sianipar, Christin Natalia; Sarwoto, Sarwoto (Community Service Progress, 2024)
This community service activity emphasizes increasing MSME sales through the use of digital marketing, especially for tofu entrepreneurs.  The aim of this activity is marketing training using Digital Marketing by providing skills that can increase family income thereby increasing welfare. The aim of this Community Service Activity is to develop MSMEs (Micro, Small and Medium Enterprises) and creative industries in the Tebing Tinggi sub-district community. Especially for jangek cracker products through Digital Marketing training.